Characterization nanosuspension formulated with Graptophyllum pictum (L.) Griff extract and hydroxyapatite as bone graft material: experimental laboratory study - Bilbalqish, Kavanila; Rianti, Devi; Sitalaksmi, Ratri Maya; Shariff, Khairul Anuar bin (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACT Introduction: Hydroxyapatite is a major component of the inorganic minerals in the hard tissues of humans and has been widely used as a biomedical ceramic material in orthopedic and dentistry applications. Adding natural ingredients such as Graptophyllum pictum can increase the anti-inflammatory properties due to the presence of phenolic compounds and alkaloids. The aim of this study was to determine the characterization nanosuspension formulated with Graptophyllum pictum (L.) Griff extract and hydroxyapatite. Methods: Nanosuspension were characterized using Scanning Electron Microscopy (SEM), Electron Dispersive X-ray analysis (EDX), Fourier Transform Infrared Spectroscopy (FTIR), and Liquid Chromatography Mass Spectrometry (LCMS). These evaluations were to reveal the surface morphology, elemental composition, functional groups, and identify the active metabolite of the nanosuspension. Results: SEM revealed the morphology agglomeration of spherical hydroxyapatite particles. The EDX analysis revealed a content of carbon, oxygen, sodium, phosphorus, chlorine, potassium, and calcium with Ca/P ratio 1.47. The FTIR analysis identified hydroxyl, water molecules, carbonate, carbonyl, and phosphate groups in the sample. LC-MS analysis identified 49 active metabolites such as phenols, alkaloid, fatty acids and their derivatives, amino acids, carbohydrates, carboxylic acids, alcohols, and ketones from the sample. Conclusion: The characteristics of nanosuspension formulated with Graptophyllum pictum (L.) Griff extract and hydroxyapatite are similar to those of natural bones. Keywordscharacterization, Graptophyllum pictum, hydroxyapatite, nanosuspension Karakterisasi nano suspensi ekstrak Graptophyllum pictum (L.) Griff dan hidroksiapatit sebagai material bone graft: penelitian eksperimental laboratoris ABSTRAK Pendahuluan: Hidroksiapatit merupakan komponen utama mineral anorganik pada jaringan keras manusia dan telah banyak digunakan sebagai keramik di bidang biomedis ortopedi dan kedokteran gigi. Penambahan bahan alami seperti Graptophyllum pictum dapat meningkatkan sifat antiinflamasi karena adanya senyawa fenolik dan alkaloid. Tujuan penelitian ini adalah mengetahui karakterisasi nanosuspensi yang diformulasikan dengan ekstrak Graptophyllum pictum (L.) Griff dan hidroksiapatit. Metode: Nanosuspensi dikarakterisasi menggunakan Scanning Electron Microscopy (SEM), Electron Dispersive X-ray analysis (EDX), Fourier Transform Independent Spectroskopi (FTIR), dan Liquid Chromatography Mass Spectrometry (LCMS). Evaluasi ini dilakukan untuk menunjukkan morfologi permukaan, komposisi unsur, gugus fungsi, dan mengidentifikasi metabolit aktif nanosuspensi. Hasil: SEM menunjukkan aglomerasi morfologi partikel hidroksiapatit berbentuk bulat. Analisis EDX menunjukkan kandungan karbon, oksigen, natrium, fosfor, klorin, kalium, dan kalsium dengan rasio Ca/P 1,47. Analisis FTIR mengidentifikasi gugus hidroksil, molekul air, karbonat, karbonil, dan fosfat dalam sampel. Analisis LC-MS mengidentifikasi 49 metabolit aktif seperti fenol, alkaloid, asam lemak dan turunannya, asam amino, karbohidrat, asam karboksilat, alkohol, dan keton dari sampel. Simpulan: Karakteristik nanosuspensi yang diformulasikan dengan ekstrak Graptophyllum pictum (L.) Griff dan hidroksiapatit mirip dengan tulang alami. Kata kuncikarakterisasi, Graptophyllum pictum, hidroksiapatit, nanosuspensi